2009
DOI: 10.5483/bmbrep.2009.42.6.350
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic properties of the N- and C-terminal halves of human hexokinase II

Abstract: Although previous studies on hexokinase (HK) II indicate both the N-and C-terminal halves are catalytically active, we show in this study the N-terminal half is significantly more catalytic than the C-terminal half in addition to having a significantly higher Km for ATP and Glu. Furthermore, truncated forms of intact HK II lacking its first N-terminal 18 amino acids (Δ18) and a truncated N-terminal half lacking its first 18 amino acids (Δ18N) have higher catalytic activity than other mutants tested. Similar re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 26 publications
6
20
0
Order By: Relevance
“…In considering the mechanism by which phosphorylation of HK-II at Thr-473 leads to an increase in mitochondrial HK-II binding, we determined whether dissociation of HK-II induced by G-6P was affected by phosphorylation. We found that mitochondrial binding of WT HK-II is inhibited in the range of 0.1–3 m m , which is in agreement with G-6P concentration increases of ∼0.17 to ∼1.3 m m in perfused working heart (52) and with the reported IC 50 of G-6P versus HK-II (53, 54). Our finding that the T473D mutant is more resistant to G-6P-dependent dissociation than the WT or the non-phosphorylatable mutant (T473A, Fig 6, A and B ) strongly suggests that phosphorylation of Thr-473 decreases the sensitivity of HK-II to G-6P-induced mitochondrial dissociation and, thereby, increases mitochondrial HK-II.…”
Section: Discussionsupporting
confidence: 89%
“…In considering the mechanism by which phosphorylation of HK-II at Thr-473 leads to an increase in mitochondrial HK-II binding, we determined whether dissociation of HK-II induced by G-6P was affected by phosphorylation. We found that mitochondrial binding of WT HK-II is inhibited in the range of 0.1–3 m m , which is in agreement with G-6P concentration increases of ∼0.17 to ∼1.3 m m in perfused working heart (52) and with the reported IC 50 of G-6P versus HK-II (53, 54). Our finding that the T473D mutant is more resistant to G-6P-dependent dissociation than the WT or the non-phosphorylatable mutant (T473A, Fig 6, A and B ) strongly suggests that phosphorylation of Thr-473 decreases the sensitivity of HK-II to G-6P-induced mitochondrial dissociation and, thereby, increases mitochondrial HK-II.…”
Section: Discussionsupporting
confidence: 89%
“…A promising strategy has been to use pHK, a peptide that corresponds to the VDAC‐binding N‐terminal 15 aa of HKII, to selectively dissociate HKII from mitochondria to inhibit activity of the enzyme (60) and trigger apoptosis (16). As pHK is poorly cell permeable (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, whereas elevated levels of mitochondria‐associated HKII are needed to maintain the high glycolytic rates that are necessary for energy production and biomolecule synthesis in rapidly dividing cancer cells, noncancerous cells rely on oxphos as their primary energy‐generating pathway (1, 3, 14, 15). Thus, dissociation of HKII from mitochondria, which inhibits the enzyme's activity (60), is far less detrimental to noncancerous cells compared with cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…A continuous supply of glucose to HK maintains this activity at a constant level and controls the flux through the mitochondrial electron transport chain, influencing mitochondrial ROS production [152]. HK binds through hydrophobic interaction to VDAC1, the prevalent pore protein in the outer mitochondrial membrane [24, 82, 143146], thereby assuring and gaining a preferential access to ATP [82, 150, 153]. Translocation of HK2 from the cytosol to the mitochondria is regulated through phosphorylation of HK by Akt [141]; HK2 only binds VDAC after phosphorylation by Akt [151, 152].…”
Section: Effects Of Jasmonates On Mammalian Cancer Cellsmentioning
confidence: 99%